2020
DOI: 10.31557/apjcp.2020.21.5.1441
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Transanal Drainage Tube for the Prevention of Anastomotic Leakage after Laparoscopic Low Anterior Resection for Rectal Cancer

Abstract: Background and Objective: Anastomotic leakage is one of the most serious complications after laparoscopic low anterior resection Low Anterior Resection (LAR) for rectal cancers. The purpose of this study was to evaluate the effectiveness of a transanal drainage tube placed for the prevention of anastomotic leakage after laparoscopic LAR. Methods: The clinical data of 220 patients with rectal cancer who underwent laparoscopic LAR using the double stapling technique

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…According to the ROBINS‐I tool and the Cochrane risk‐of‐bias assessment tool, 11 cohort studies [27–33, 34–36, 39] were ranked as low risk of bias, five cohort studies [24, 25, 34, 37, 40] were ranked as moderate risk of bias and one cohort study [38] as serious risk of bias (Figure 2). The randomization of the RCTs [16, 22, 23] was implemented by a central automated randomization website and allocation was concealed using closed envelopes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the ROBINS‐I tool and the Cochrane risk‐of‐bias assessment tool, 11 cohort studies [27–33, 34–36, 39] were ranked as low risk of bias, five cohort studies [24, 25, 34, 37, 40] were ranked as moderate risk of bias and one cohort study [38] as serious risk of bias (Figure 2). The randomization of the RCTs [16, 22, 23] was implemented by a central automated randomization website and allocation was concealed using closed envelopes.…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen studies [24, 25, 27–40] reported AL rate as an outcome measure. Patients receiving TDT had a significantly decreased risk of anastomotic leak compared with the non‐TDT group; 7.3% (123/1694) of TDT patients reported AL at follow‐up compared to 12.6% (221/1751) of the non‐TDT group with a pooled OR of 0.44 (95% CI 0.30–0.64, P < 0.0001; Figure 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to stent therapy, studies have shown that TIDTs, which are placed 3-5 cm above the anastomosis, can be used to prevent anastomotic leakage after rectal cancer resection[ 14 , 18 ], and some studies have shown that anastomotic leakage cannot be prevented[ 19 ]. After the intestinal cavity is sealed by the balloon, artificial intestinal obstruction may occur, which easily promotes intestinal peristalsis, and the TIDTs are easily discharged.…”
Section: Discussionmentioning
confidence: 99%
“…Rectal cancer is one of the most common malignancies worldwide (Wang et al, 2020). Recently, laparoscopic low anterior resection (LAR) with total mesorectal excision (TME) has been commonly performed for middle and lower rectal cancers (Heald and Ryall, 1986;Peeters et al, 2005).…”
Section: Introductionmentioning
confidence: 99%